The Structure of Shariah Governance in Islamic Banking Industry: A Theoretical Review - Jan, Ahmad Ali; Lai, Fong-woon; Mat Isa, Muhammad Pisol Bin; Hamad, Salaheldin (International Journal of Psychosocial Rehabilitation, 2020)
Shariah regulations play a fundamental role in the governance of the Islamic banking industry. The Shariah board is an essential tool of the Shariah governance. This paper aims to investigate the efficacy of Shariah governance in Islamic banks in the evolving regulatory frameworks and sheds some light on the Islamic corporate governance. This study theoretically compares different Shariah governance structures, the centralized Shariah structure followed by Pakistan, Malaysia, Iran and the decentralized Shariah structure in Gulf Cooperation Council (GCC) countries. The Shariah board’s independence in its supervisory role is the main feature of an effective Shariah governance framework. In terms of the efficiency and credibility of Islamic banks, the centralized Shariah structure seems to be more advantageous for the industry. The centralized Shariah structure ensures consistency and uniformity in Islamic banking in issuing the fatwas (Shariah opinions). It improves the Shariah board’s role and independence that can analyze divergence issues across the entire Shariah board. This study could be helpful to researchers, practitioners, regulators, and academicians in understanding the true picture of Shariah governance. This paper emphasizes the importance of investigating the Shariah governance in Islamic banking. The study gives a direction to empirically investigate the role of centralized and decentralized Shariah structure on Islamic banks’ performance.